The Role of Inequality in Indonesia: Does Fiscal Decentralization Matter? - Nunung Zahrotul Hayat; Mahrus Lutfi Adi Kurniawan; Wing-Keung Wong (Universitas Negeri Malang, 2023)
This research explores the role of inequality because inequality has long-term effects on social and economic conditions and has an impact on the decentralization process. There are two models developed in which inequality is the regressor of regional income and inequality is the regressor. The panel seemingly unrelated regression is applied to produce consistent coefficient parameters. The results of research on model 1 show that inequality has a negative effect on regional income and on model 2 shows that fiscal decentralization with government spending has a positive effect on inequality and special allocation funds have a negative effect on inequality. The implication of research is that fiscal decentralization can reduce the level of inequality if it is transferred and prioritizes poor or disadvantaged areas.